Euthanasia and small‐population management: development of transparent processes, good governance and a practical application. Issue 1 (10th May 2018) - Walraven, E.; Andrew, P.; Boyle, N.; Duffy, S.
Abstract : The issue of euthanasia is one of the more challenging aspects of managing populations of animals in human care. The practice of animal euthanasia is a matter of sensitivity within zoos and the wider community. Decisions are centred on the ethical obligations towards the animals in our care, and the acknowledgement that individual animals matter to our staff, volunteers and visitors. In order to facilitate timely decisions in an objective way to benefit the animal population as a whole, and the need to dedicate resources towards the best possible conservation outcomes, Taronga Conservation Society Australia (Taronga) initiated a process of review in 2009. This review resulted in the development of a Euthanasia Decision Key to assist the process in an inclusive way. Taronga recognizes a responsibility not only to the welfare of the individual but also to the resilience of the animal populations in its care. In some species the resilience of a population is prioritized over the interests, but not welfare, of the individual. Taronga used a combination of considerations underpinned by the life‐history parameters of each species as a guide to formulate decisions when these interests are in potential conflict. Euthanasia is a last resort that is only applied once all other alternatives have been considered. Taronga's approach to welfare and animal care is continually evolving to ensure contemporary practice. This paper describes the decision‐making process that was developed, and the ethical underpinnings inherent within it. The approach and processes continue to evolve to remain contemporary with emerging laws, ethics and societal expectations. Abstract : Euthanasia is one of the more challenging aspects of managing populations of animals in human care. Decisions are centred on the ethical obligations towards the animals, and the acknowledgement that individual animals matter to staff, volunteers and visitors. In order to facilitate timely decisions in an objective way to benefit the well‐being of the individual animals and populations, and the need to dedicate resources towards the best possible conservation outcomes, Taronga Conservation Society Australia has developed a Euthanasia Decision Key to assist the process in an inclusive way. Taronga uses a combination of considerations underpinned by the life‐history parameters of each species as a guide to formulate decisions. This paper describes the decision‐making process that was developed for the purposes of long‐term population viability. (Logo: Taronga Conservation Society Australia)